Bluecoats & Tar Heels : soldiers and civilians in Reconstruction North Carolina - Bradley, Mark L. (New directions in southern history., 2009)
In Bluecoats and Tar Heels: Soldiers and Civilians in Reconstruction North Carolina, Mark L. Bradley examines the complex relationship between U.S. Army soldiers and North Carolina civilians after the Civil War. Postwar violence and political instability led the federal government to deploy elements of the U.S. Army in the Tar Heel State, but their twelve-year occupation was marked by uneven success: it proved more adept at conciliating white ex-Confederates than at protecting the civil and political rights of black Carolinians. Bluecoats and Tar Heels is the first book to focus on the army's.